The influence of herring (Clupea harengus) biomass and distribution on killer whale (Orcinus orca) movements on the Norwegian shelf - Vogel, Emma F. (UiT Norges arktiske universitet, 2020)
Killer whales (Orcinus orca) have a cosmopolitan distribution with a broad diet ranging from fish to marine mammals. Regional populations show local prey specialization and their movements are tightly linked to those of their prey. Norwegian killer whales are known to feed extensively on Norwegian spring spawning (NSS) herring (Clupea harengus). Over the last decade, killer whales have begun to readily been observed feeding on high concentrations of overwintering herring in some fjords of northern Norway. Killer whale offshore behavior is less well understood, specifically their reliance on herring as a prey resource outside of the fjord systems. We used movement parameters extracted from 29 killer whale satellite tracks on the Norwegian shelf and related their movements to herring biomass and distribution. Two techniques were used to estimate herring biomass, one based on survey data, and the other based on a simulated ecosystem model. Mixed effects modeling was then used to estimate the effect of herring biomass and diel variations in light levels, on the whales’ movement parameters. We found that killer whales tend to follow the herring when they leave their coastal overwintering areas for their spawning grounds. Individual whale movement characteristics changed from fast directed travel in areas of low herring biomass towards slower non-directed travel when relative herring biomass increased. This suggests that whales feed on herring when they encounter dense concentrations on the Norwegian shelf. Relationships between killer whale movement patterns and herring biomass were consistent for both survey- and simulation-based herring fields. This highlights the potential for using model-based estimates of prey distribution when interpreting predator behavior. We conclude that NSS herring constitutes an important prey resource for killer whales, both during the overwintering and subsequently until the end of the spawning events. Killer whale movements can potentially assist in identifying previously unknown NSS ...